PERANAN GELOMBANG PANJANG TERHADAP SIRKULASI ARUS GLOBAL - Fendry Yandi Samuel Mamengko (FMIPA Universitas Papua, 2007)
The global surface current system forms a large scala current circulation pattern known as gyra, which occurs in the Pasific, Hindia, and Atlantic oceans. At the nothern equator, the gyra circulation is counterclockwise, while it is anti counterclockwise at the southern equator. The trade wind crossing the Equatorial ocean causes a different slope and influences the slope form. The response of the sea level slope can be only described by the sea level pertubation concept that the disturbance moves as pulse wave which travel alongside equatorial ocean. The effects of the Rossby and Kelvin waves propagation on the ocean circulation depend on the lattitude. At the middle and high lattitudes, the Rossby wave experiences the change of the surface wind stress which has more influence in the ocean near western boundaries than that in the near eastern boundaries. At low lattitude, the Rossby and Kelvin waves propagations is located at the equatorial wave guide. Along the equatorial wave guide, the Kelvin wave propagates easterly. This wave is then split into 2 directions as the wave moves towards the eastern boundary. The first direction goes to the northern equator. The other moves towards the southern equator, which eventually becomes the coastal Kelvin wave. A part of the Kelvin wave is reflected to produce the equatorial Rossby wave. Because of the equator plays important roles as wave guides, the low lattitude ocean responds more to the variability of the wind flow than that at the high lattitude.